Coal Bumps in an Eastern Kentucky Coal Mine 1989 to 1997 - John Hoelle (International Conference on Ground Control in Mining, 2008)
Coal mines in southern West Virginia, south-western Virginia and eastern Kentucky have experienced coal bumps at least since 1933. Most of the bumps have occurred due to high cover, strong roof and floor strata and stress concentrations due to the mining sequence. A longwall mine in eastern Kentucky first experienced coal bumps on the tailgate side of the longwall face in 1989. The bumps continued until 1996. The bumps were the result of: Thick overburden up to 2200 feet Strong roof and floor (strata strengths up to 25,600 psi UCS and elasticity modulus up to 4,800,000 psi Previous over-mining in places Sandstone channels Not all characteristics occurred simultaneously. The bumps produced seismic events recorded up to 4.3 (Richter scale magnitude), and damaged pillars that were up to 147 by 152 feet in size.